Studies in philology linguistics, literature and cultural studies in modern languages - Mármol, Gema Alcaraz; Arnao, Mar Jiménez-Cervantes (Cambridge Scholars Publishing, 2014)
Linguistics, Literature and Cultural Studies are the three main research areas within Philology. Scientific production, such as conferences and journals, has tended towards specialization, and has been traditionally classified according to separate disciplines and languages. However, this volume offers a holistic view of the wide area of Philology, therefore allowing the permeability of the three areas mentioned above. As such, this book shows that the line that separates Linguistics, Literature and Cultural Studies is actually very thin. This volume is composed of a miscellanea of philologica.